REMOTE CONTROL OF SUBSTANCE QUANTITY AND CONSUMPTION - Akhmadaliyev Anvarbek Alijon o’g’li (Journal of new century innovations, 2023)
Abstract: Consumption measuring devices measure instantaneous consumption and control the work of technological modes, automatically adjust at any stage of the technological process. CDMA (Code Division Multiple Access), GSM (Global Systems for Mobile Communications), TDMA (Time Division Multiple Access), 802.11, WAP (Wireless Application Protocol) wireless technology protocol), 3G and 4G (third and fourth generation technologies), GPRS (General Packet Radio Service, data packet transmission service), Bluetooth (medium and short distance network), EDGE (Enhanced Data) Rates for GSM Evolution, improved GSM network).